Evidence-based Management of Major Bleeding in Patients Receiving Direct Oral Anticoagulants: An Updated Narrative Review on the Role of Specific Reversal Agents - Zohair Al Aseri FRCPC EM, CCM; Farjah H. AlGahtani MD, MPH; Majid F. Bakheet MD; Ahmed H. Al-Jedai PharmD; Sarah Almubrik MD (SAGE Publishing, 2023)
The indications of direct oral anticoagulants (DOACs) have expanded over the past 15 years. DOACs are effective and safe oral anticoagulants associated with lower bleeding risks and mortality than vitamin K antagonists. However, DOAC users are prone to a considerable bleeding risk, which can occur at critical sites or lead to severe life-threatening conditions. Recent statistics indicated that major bleeding occurs in up to 6.62 DOAC users per 100 treatment years. With the increased use of DOACs in clinical practice, DOAC-associated major bleeding is expected to be encountered more frequently in the emergency department. The current international guidelines recommend specific reversal agents for the management of DOAC users with severe bleeding to reverse the anticoagulant effect and restore normal hemostasis. An individualized assessment was incorporated in specific clinical situations to guide the decision pathway of major bleeding management. However, specific reversal agents are unavailable or have limited availability in many countries, which is expected to negatively impact the clinical outcomes of DOAC-associated major bleeding. Limited real-world evidence is available from these countries regarding the clinical outcomes of patients with DOAC-associated major bleeding. This narrative review provided an updated assessment of the evidence-based approaches for the management of major bleeding in DOAC users. We also explored the clinical outcomes of patients with major bleeding from clinical settings where specific reversal agents are unavailable.